Novelties in Microlicia (Melastomataceae, Lavoisiereae) endemic to the campo rupestre of Guiné, Chapada Diamantina, Bahia, Brazil - Pacifico, Ricardo; Almeda, Frank; Gali, Lorena; Fidanza, Karina (Phytotaxa, 2022)
Two species of the Neotropical genus Microlicia are here proposed as new (Microlicia bicolor and M. pataroi). Both species are restricted to the Beco do Guiné trail to Vale do Pati in the municipality of Mucugê, state of Bahia, Brazil. Diagnoses, line drawings, notes on diagnostic characters, habitat and phenology, conservation assessments, and distribution maps are provided.